Associations between state-level restorative justice policies and mental health among women survivors of intimate partner violence - Laurel Sharpless; Trace Kershaw; Tiara C. Willie (Elsevier, 2022)
Intimate partner violence (IPV) can impact the mental health of survivors; however, little is known about the role of state-level restorative justice policies. Restorative justice policies are survivor-centered justice approaches focused on repairing harm between the survivor and perpetrator, which may buffer mental health outcomes among IPV survivors. Furthermore, the impact of restorative justice policies on mental health may be influenced by the degree of state-level support for policy implementation. This study examined the relationship between (1) IPV exposure and mental health and whether restorative justice policies moderate the relationship; and (2) whether restorative justice policy implementation support moderates the relationship between IPV and mental health among women. Data on state restorative justice policies were drawn from a U.S. restorative justice legislation database. Individual-level data on 5104 adult women were collected from the 2010 National Intimate Partner and Sexual Violence Survey (NISVS), a nationally representative study of noninstitutionalized adult women and men. Generalized estimating equation (GEE) models were conducted to examine associations between IPV, state-level restorative justice policies, restorative justice policy implementation support, and perceived mental health (N ​= ​5104). Women who experienced IPV had worse perceived mental health compared to women without IPV (b [95% CI] ​= ​−0.13 [−0.15, −0.11], p ​< ​0.001). The inverse relationship between IPV and survivor mental health was attenuated in states with a restorative justice policy vs. states without (b [95% CI] ​= ​0.05 [0.00, 0.09], p ​= ​0.038). The relationship between IPV and worse survivor mental health was weakest in states with high restorative justice policy implementation support (b [95% CI] ​= ​0.03 [0.00, 0.05], p ​= ​0.032). Restorative justice policies may serve as a scalable tool to reduce negative mental health sequelae related to IPV and strengthen current justice responses for IPV survivors.